A rare cause of short stature: Kenny-Caffey syndrome type 2 – a case report and literature review - Kaleta, Dagmara; Zapolnik, Paweł; Mazur, Anna; Pyrkosz, Antoni (Pediatria Polska - Polish Journal of Paediatrics, 2020)
Kenny-Caffey syndrome type 2 is a very rare disease characterized by short stature, skeleton and eye abnormalities, hypoparathyroidism, hypocalcemia, and normal intellectual development. It is caused by a mutation in the FAM111A gene and inherited in an autosomal dominant way. It occurs at a frequency of 1 : 1 000 000. Less than 100 cases had been described to date. Treatment in this disease is only symptomatic and the use of growth hormone does not give satisfying effects. We present a case of a 12-year-old boy with short stature, hypoparathyroidism, hypothyroidism, and hyperopia. The next-generation sequencing study revealed a mutation (R569H) in one allele of the above-mentioned gene. On the basis of the clinical picture and special investigations results, Kenny-Caffey syndrome type 2 was diagnosed.